Market information - the need for speed - Mukhebi, Adrian (Technical Centre for Agricultural and Rural Cooperation, 2005)
Dr Adrian Mukhebi of the Kenya Agricultural Commodity Exchange, on how mobile phone networks are enabling timely market information to reach remote rural communities in Kenya.